2018
DOI: 10.1074/jbc.ra118.002414
|View full text |Cite
|
Sign up to set email alerts
|

Functional proteasome complex is required for turnover of islet amyloid polypeptide in pancreatic β-cells

Abstract: Human islet amyloid polypeptide (hIAPP) is the principal constituent of amyloid deposits and toxic oligomers in the pancreatic islets. Together with hyperglycemia, hIAPP-derived oligomers and aggregates are important culprits in type 2 diabetes mellitus (T2DM). Here, we explored the role of the cell's main proteolytic complex, the proteasome, in hIAPP turnover in normal and stressed β-cells evoked by chronic hyperglycemia. Moderate inhibition (10-35%) of proteasome activity/function in cultured human islets by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…Recent papers have evidenced that 20S proteasome activation may protect cells from amyloid proteotoxic stress. [53,54] Accumulating evidence suggests that a deranged equilibrium between production and clearance of the amyloid Aβ peptide -which plays a pivotal role in AD pathogenesis -could result from a declined proteasome activity. Based on this hypothesis, an increasingly large number of reports focuses on the possibility to modulate proteasome activity by drug treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Recent papers have evidenced that 20S proteasome activation may protect cells from amyloid proteotoxic stress. [53,54] Accumulating evidence suggests that a deranged equilibrium between production and clearance of the amyloid Aβ peptide -which plays a pivotal role in AD pathogenesis -could result from a declined proteasome activity. Based on this hypothesis, an increasingly large number of reports focuses on the possibility to modulate proteasome activity by drug treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The authors showed that the altered protein-lipid composition of the EVs is the main reason for this discrepancy ( 95 ). However, Chatterjee et al have shown that β-cells from T2DM patients have a dysfunctional proteasome complex that fails to degrade pancreatic IAPP, whereby amyloid formation is induced ( 96 ). Furthermore, in T2DM patients, lipids accelerate the formation of fibrillary IAPP, which aggravates islet cell damage ( 97 ).…”
Section: Effects Of T2dm On the Digestive Systemmentioning
confidence: 99%
“…Aggregated IAPP have cytotoxic properties [24,25] and their presence is associated with β-cell failure, loss of β-cells, and correlates with severity of T2DM in affected patients [15,26,27]. Recently, it has been demonstrated that impaired intracellular turnover of IAPP by proteasomes and autophagy contribute to the accumulation of toxic IAPP, leading to β-cell death during T2DM [28,29]. Therefore, effective therapeutic strategies for disease modifying treatment of T2DM are urgently needed.…”
Section: Discussionmentioning
confidence: 99%